2020
DOI: 10.2112/si95-042.1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Measurement and Automatic Processing of In-situ Wave Impact Pressure Data

Abstract: Although wave impact has been extensively studied in laboratories, field studies are comparatively rare. However, as real wave impacts are influenced by numerous environmental factors, complementing physical studies with in-situ data is necessary to better understand the processes at stake and provide reliable tools for coastal engineers. One of the main reasons for the lack of field data is the extreme conditions usually met on site. Nowadays, technology allows to set up stations able to resist those conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The procedure of pressure acquisition and post-processing is described in detail in [18]. The acquisition station records wave impact pressure hourly in 10 minutes burst, with a sampling frequency F e = 10000 Hz.…”
Section: Wave Impact Pressure Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure of pressure acquisition and post-processing is described in detail in [18]. The acquisition station records wave impact pressure hourly in 10 minutes burst, with a sampling frequency F e = 10000 Hz.…”
Section: Wave Impact Pressure Datamentioning
confidence: 99%
“…Note that with the trapezoidal integration rule, sensor 0 has a major weight in the determination of the force as z 1 −z 0 = 1.9 m while the next ∆z = 0.2 m, with z i the altitude of the sensors. The bursts have been automatically processed by d'Amico et al [18], 152999 impacts were identified overall in 2018-2019.…”
Section: Wave Impact Pressure Datamentioning
confidence: 99%
See 1 more Smart Citation